Redução de filas em caixas de supermercados de Aracaju/SE - Monteiro, Luciano Fernandes (2018)
The solution to reduce the formation of large queues in supermarkets requires logistic and operational studies, with applications of simulation techniques to analyze and quantify the waiting time of customers during the payment of their purchases. This study intends to propose changes in the operational processes of three supermarkets in the city of Aracaju / SE, aiming to offer quality services and satisfaction to its customers. This work aimed to detect and analyze the possible causes related to the waiting time of customers in supermarket box queues. The information was obtained locally through collected data, using digital chronometer for time measurements. Data was stored and analyzed using Microsoft Excel. As for the modeling and graphing, we used Flowcharts and Petri Net which helped the modeler graph the process. Improvement solutions were proposed for the problems that generate increase in waiting time, such as: operational, disagreements in queues, inattentive customers, concluding that queues are complex and require detailed studies.